2007
DOI: 10.1080/08860220601095827
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin, Resistin, and Lipid Levels in Patients with End Stage Renal Failure with Regard to Dialysis Modality

Abstract: Serum leptin, resistin, triglycerides, and total cholesterol levels were higher in CAPD patients. Leptin levels were positively correlated with TATM, serum triglycerides, total cholesterol, and LDLc levels in dialysis patients. Resistin levels were positively correlated with TATM and triglycerides in CAPD patients. Glucose load during CAPD may be an important factor in increased in leptin, resistin, triglycerides, and total cholesterol levels in CAPD patients. These results highlight the importance of leptin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…Renal dysfunction has been associated with elevated resistin levels(3537), though in our study SLE was associated with higher resistin levels independent of GFR. In addition, CRP and Hcy have recently been shown to upregulate resistin production from PBMC and adipocytes, respectively(18, 38).…”
Section: Discussioncontrasting
confidence: 67%
“…Renal dysfunction has been associated with elevated resistin levels(3537), though in our study SLE was associated with higher resistin levels independent of GFR. In addition, CRP and Hcy have recently been shown to upregulate resistin production from PBMC and adipocytes, respectively(18, 38).…”
Section: Discussioncontrasting
confidence: 67%
“…Besides, omentin is a relatively large protein, 40 kDa [19], which during hemodialysis may not be significantly cleared from plasma. Currently there is no study supporting our estimation related to omentin excretion, but generally most adipokines such as adiponectin, visfatin and resistin are elevated in patients with CKD, likely owing to decreased renal excretion [20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Few studies on resistin observed longitudinal clinical outcomes unlike studies on leptin or adiponectin. Some reports have shown no correlation between resistin and inflammatory cytokines (26, 27). It is possible that resistin levels may predict poor hospital-free survival independently of inflammation in our hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%